Giant cell reparative granuloma concurrent with squamous cell carcinoma of the temporal bone: A case report and review of the literature - Noppadol Larbcharoensub (2018)
A case of giant cell reparative granuloma concurrent with squamous cell carcinoma of the right temporal bone in a 44-year-old man with clinically presenting otorrhea from the mass of the right acoustic canal with hearing loss is reported. The histopathological examination of the lesion characterizes by multi-nucleated giant cells with in a fibroblastic stroma and area of keratinizing squamous cell carcinoma. GCRG may have been a local reaction provoked by the squamous cell carcinoma. Clinical and pathological features with briefly reviewed relevant literatures of temporal GCRG describing 24 cases are discussed. The patients have the mean age of 34.8 years. The ages of the patients ranged from 4 months to 72 years old. Temporal bone GCRG shows a male predilection of approximately 3:1. The frequently presenting symptoms of temporal bone GCRG are hearing loss, mass, tinnitus, otalgia, otorrhea, vertigo, headache, facial weakness, and diplopia. This is the first reported description in the literature of temporal bone GCRG concurrent with squamous cell carcinoma.